(3eYGde GdGSJQGJjLjI ddJfejI GdGbJUGOjI h GdbhejI aj GdHdOGf GdfGejI (B/s - (3GdGbOGMi, gTGe eMehOs ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2009)
(3bVGjG GdJNda h NUGFUg , GdJfejI GdGbJUGOjI , ebGjjS Gdfeh GdGbJUGOjI h GdGLJeGYjI h ESJQGJjLjI GdJfejI , GdJcGed GdGbJUGOOj , CReI GdJcGed h GdJfejI , GdJNWjW ddJfejI , GdJNWjW GdGLJeGYj , eTcdGJ GdJhGab GdGLJeGYjs
(3eQGLY U(B.291 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdHdOGf GdfGejIs; (3GdJNWjWs; (3GdJNdas; (3GdJfejI GdGbJUGOjIs